1998
DOI: 10.1038/nm0398-336
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor is essential for corpus luteum angiogenesis

Abstract: The development and endocrine function of the ovarian corpus luteum (CL) are dependent on the growth of new capillary vessels. Although several molecules have been implicated as mediators of CL angiogenesis, at present there is no direct evidence for the involvement of any. Here we report the unexpected finding that treatment with truncated soluble Flt-1 receptors, which inhibit vascular endothelial growth factor (VEGF) bioactivity, resulted in virtually complete suppression of CL angiogenesis in a rat model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
362
0
23

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(394 citation statements)
references
References 17 publications
9
362
0
23
Order By: Relevance
“…On the other hand, the results of a phase I clinical trial with VEGF inhibitors showed that these agents were well tolerated, 34 indicating a marginal role for VEGF signalling in normal organs under physiological conditions except the ovary during the menstrual cycle. 35 Another problem for the clinical use of a type II CRAd is that the relevant promoter activity in each tumor should be evaluated before treatment. From previous reports as well as our results, it is clear that tumors with low promoter activity are resistant to type II CRAds containing that promoter.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of a phase I clinical trial with VEGF inhibitors showed that these agents were well tolerated, 34 indicating a marginal role for VEGF signalling in normal organs under physiological conditions except the ovary during the menstrual cycle. 35 Another problem for the clinical use of a type II CRAd is that the relevant promoter activity in each tumor should be evaluated before treatment. From previous reports as well as our results, it is clear that tumors with low promoter activity are resistant to type II CRAds containing that promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Given the synchronized nature of neovascularization in this cyclical process, it is assumed that angiogenic growth factor expression is induced by steroid hormones and regulates blood vessel formation in reproductive organogenesis. [113][114][115][116] Indeed, physiological changes in the reproductive tract during the normal menstrual cycle 28 as well as physiological and pathological symptoms, including telangiectasia of pregnancy 117 and telangiectasia in postsclerotherapy patients receiving gonadal hormones, 118 are all associated with elevated levels of serum estradiol.…”
Section: Hormone-regulated Neovascularizationmentioning
confidence: 99%
“…Treatment with either AZD2932 (VEGFR and PDGFR inhibitor; or a combination of AZD2171 (Cediranib; VEGFR inhibitor; Wedge et al 2005) and AZ12585313 (PDGFRa and b inhibitor), which were dosed to achieve approximately 1:1 inhibition of the PDGFR and VEFGR receptors, resulted in avascular necrosis and a reduction in the number and size of corpora lutea in the ovary-essentially identical changes to those induced by VEGFR inhibition alone (Ferrara et al 1998) and similar to those induced by Sunitinib, which inhibits both VEGFR and PDGFR receptors (as well as c-Kit, FLT3, and RET receptors; Patyna et al 2008). These experiments therefore confirmed that during ovarian angiogenesis, VEGFR inhibition was dominant to PDGFR inhibition, consistent with the sequential cascade of endothelial vascularization followed by pericyte stabilization during angiogenesis.…”
Section: Discussionmentioning
confidence: 99%